On a General Class of Multiple Eulerian Integrals with Multivariable Aleph-Functions (Global Journal of Science Frontier Research, 2017)
Abstract not found
Keywords: multivariable aleph-function; multiple eulerian integral; class of polynomials; the sequence of functions; aleph-function of two variables; multivaria